2010
DOI: 10.1007/s00134-010-2082-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive pressure support ventilation and CPAP in cardiogenic pulmonary edema: a multicenter randomized study in the emergency department

Abstract: During CPE, NIPSV accelerates the improvement of respiratory failure compared to CPAP but does not affect primary clinical outcome either in overall population or in subgroups of patients with hypercapnia or those with high B-type natriuretic peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
1
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 25 publications
(32 reference statements)
3
38
1
14
Order By: Relevance
“…(13) Nouira et al (11) observed similar effects of BiPAP use compared to CPAP on EI outcomes. Nonetheless, BiPAP is associated with faster improvements in respiratory failure in APE patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…(13) Nouira et al (11) observed similar effects of BiPAP use compared to CPAP on EI outcomes. Nonetheless, BiPAP is associated with faster improvements in respiratory failure in APE patients.…”
Section: Discussionmentioning
confidence: 92%
“…(10) The main indications for NIV are associated with chronic obstructive pulmonary disease (COPD) exacerbation and acute cardiogenic pulmonary edema (APE). (4,(11)(12)(13)(14) The main contraindications include a decreased level of consciousness, psychomotor agitation, hemodynamic instability, obstruction and trauma of the upper airway and undrained pneumothorax. (1,8) The most discussed NIV methods include continuous positive airway pressure (CPAP), which uses a single pressure level during both phases of the respiratory cycle, and ventilation with two levels of pressure (BiPAP -bi-level positive airway pressure), which uses an inspiratory positive airway pressure (IPAP) and an expiratory positive airway pressure (EPAP).…”
Section: Introductionmentioning
confidence: 99%
“…In a comparison of CPAP with Bi-PAP, the latter demonstrated more rapid recovery of respiratory and hemodynamic parameters [19], but Bi-PAP associated with an increased incidence of acute myocardial infarction [14]. Recently, Nouira et al, [20] showed that Bi-PAP improves respiratory failure, while, Masip et al, [21] showed a decrease in intubation rate in Bi-PAP group when compared with CPAP. However, other studies [10,22] failed to demonstrate significant differences in vital signs, blood gases, and rate of myocardial infarction between two modes of ventilations and between Bi-PAPA and oxygen therapy [23].…”
Section: Introductionmentioning
confidence: 98%
“…In this issue of intensive care medicine, Nouira and colleagues [30] reported the results of another prospective, multicenter, randomized trial comparing the use of NIPPSV versus CPAP during the emergency care of CPE. The study was very well performed and the patients were carefully screened and selected.…”
mentioning
confidence: 99%
“…Taking into account previous literature and the new data provided by Nouira et al [30], what conclusions can be drawn from a clinical point of view? First, the use of NIV during acute respiratory distress is still an issue of importance.…”
mentioning
confidence: 99%